In search of a new paradigm for innovation, free markets, and regulation - Acemoglu, Daron (Henry Stewart Talks, 2024)
Political economy, Innovation, Regulation, State capacity, Legitimacy, Democratic process, Leadership vs. consensus, Technological transition, Continuous flux, Shareholder profit, Employee gains